Immunomodulator Activity of Puguntano (Picria fel-terrae Lour.) Extract in White Male Mice By Carbon Clearance Method - Rezza Fikrih Utama; Rosidah; Yuandani (Indonesian Journal of Pharmaceutical and Clinical Research, 2020)
Poguntano Herb Plants (Picria fel-terrae Lour.) contains flavonoids compounds that have been potentially to developed into immunomodulators. The purpose of this study was to determine the immunomodulatory activity of Poguntano herb extract (Picria fel-terrae Lour.), with the method of carbon clearance. n-hexane extract puguntano herb(ENHHP), extract of ethyl acetate of Poguntano herb (EEAHP), and ethanol extract of puguntano herb(EEHP) Poguntano multistage results in the test of immunomodulatory activity with a method of carbon clearance. Results showed that the EEHP 200 mg/kg BB showed a strong immunostimulation effect, EEAHP 200 mg/kg BB showed strong immunostimulation effect, ENHP 200 mg/kg BB demonstrated strong immunostimulation effect. It is thought that extract N-hexane herb Poguntano (ENHHP), extracts of ethyl herb acetate Poguntano (EEAHP), and herb ethanol extract Poguntano (EEHP) Poguntano herb may increase phagocytosis activity. Extract of ethyl acetate Poguntano herb 200 mg/kg bw (EEAHP) has the best phagocytosis activity with a value of 2.376 which indicates there is a significant difference (P < 0.05) with another treatment group.